Fe3O4-NPs/orange peel composite as magnetic heterogeneous Fenton-like catalyst towards high-efficiency degradation of methyl orange - Qiang Zhao (IWA Publishing, 2021)
Magnetite nanoparticles (Fe3O4-NPs)/orange peel (MOP) composite was prepared via one-step in-situ co-precipitation method as magnetic heterogeneous Fenton-like catalyst. The properties of MOP were characterized by scanning electron microscopy, transmission electron microscopes, Brunauer–Emmett–Teller, X-ray diffraction, Fourier-transform infrared, thermogravimetric analysis and X-ray photoelectron spectroscopy technologies. Its Fenton-like catalytic responses towards removal of methyl orange (MO) were investigated, in which the effects of initial dye concentration, pH, temperature and hydrogen peroxide dosage were studied. The MO degradation ratio up to 98.0% was obtained within 20 min in optimized conditions. The catalyst showed excellent catalytic stability exhibiting nearly 90% degradation ratio in the 10th cycle within 20 min, whereas pure Fe3O4-NPs showed only 62.5% in this stage. Due to the stabilization of complexing orange peel hydroxyl to iron oxide in the composite and its magnetic separation property, MOP composite exhibits excellent Fenton-like catalytic performance, which offers great prospects for low-cost and high-efficiency organic dye wastewater treatment. Highlights Cheap raw materials like waste biomass and common Fe salts.; Fe3O4/orange peel composite as heterogeneous Fenton-like catalyst.; 98.0% of 30 ppm MO can be degraded within 20 min in optimized conditions.; Easy separation: fast magnetic separation from aqueous solution within 1 min.; Superior cycle catalytic stability: MO (20 ppm) degradation ratio reaches up to nearly 90% within 20 min in the 10th cycle.;